Estimation method of surface texture parameters by inverse analysis of dynamic characteristics - Yoshinao KISHIMOTO (The Japan Society of Mechanical Engineers, 2017)
The surface texture describes the surface topography formed by micro asperities on a surface of a solid member. The Hertz-Mindlin theory is one of contact theories based on the mechanics of elasticity. The main parameters for the theory are the number of the asperity peaks per unit area, the radius of the curvature at the asperity peak and the standard deviation of the asperity peak heights. These parameters are collectively named as the surface texture parameters. Most of the conventional approaches to obtain these parameters are curve fittings applied on the surface texture. However, the 3D measurement with a spatial resolution of a micron is required in the measurement of the surface texture, and the measurable area is limited. This study has developed a novel method to estimate the surface texture parameters by the inverse analysis of the dynamic characteristics of the target. In the proposed method, the natural frequency of the target is obtained by the hammering test and the finite element analysis with the interfacial element based on the Hertz-Mindlin theory. Then the set of the surface texture parameters minimizing the residual between the test result and the analysis result is derived. In order to verify the proposed method, a series of hammering tests was carried out by using specimens with bolted joints. Using the test results, the surface texture parameters were estimated by the proposed method. From the estimation results, it confirmed that the calculation results of the natural frequency in the inverse analysis had good agreement with the results of the hammering test. The estimation accuracy of the proposed method was comparable to that of the 3D surface texture measurement in terms of fitting the quadratic surfaces.